Implementation of Laboratory Examination of Hypertension and Diabetes Mellitus Prolanis Patients at UPTD Sukabumi City Health Laboratory - Susanti; Rachmawati, Ike (International Journal of Psychology and Health Science, 2024)
The results of the 2018 Riskesdas for Non-Communicable Diseases (NCDs) experienced an increase in incidence from . The government, through BPJS Health, launched the prolanis program to prevent degenerative diseases. Sukabumi City Health Laboratory UPTD has provided laboratory examination services for patients with prolanis hypertension and prolanis diabetes mellitus. This research is a descriptive analysis with a cross sectional design. The research population was prolanis patients in the hypertension category and diabetes mellitus category. The sampling technique uses a total sampling of 366 samples. The number of samples in the hypertension category was 249. There were 117 patients in the diabetes mellitus category. The results of this study illustrate that the majority of patients had cholesterol, urea, creatinine and microalbumin levels in the normal range. However, there are some patients who have such high levels of HBA1c that require further monitoring and appropriate intervention to reduce the risk of health complications.